La Relación entre el Nivel de Madurez en la Gestión de Proyectos y los Resultados Caso Joy Global - Milián Gonzales, Roger (2020)
The main objective of this study was to determine the relationship between the project management maturity level and the results case Joy Global. The descriptive type and the correlational type were used as the type of research, since its purpose was to measure the degree of relationship that exists between the two study variables. The methodological design is non-experimental. For the research study the maturity level is calculated according to the 10 knowledge areas of the PMI such as integration, scope, time, cost, quality, human resources, communication, risks, acquisition and stakeholders management and the success of a project taking into account the 5 components of (Shenhar & Dvir, 2007). The results obtained reflect the direct relationship between the maturity level variable on the projects success variable within the company Joy Global (Peru).